KENDALA PENERAPAN PELAPORAN PPH PASAL 21 DAN ZAKAT SEBAGAI PENGURANG PAJAK: PENDEKATAN KUALITATIF (STUDI KASUS KARYAWAN BSI KCP SEMARANG - Imendra, Amaylia Rizky; Utami, Martiana Riawati (Mount Hope Management International Journal, 2024)
This study aims to analyze the implementation of Article 21 Income Tax and the utilization of zakat as a tax deduction among employees of Bank Syariah Indonesia (BSI). Article 21 Income Tax is an income tax levied on earnings related to employment, while zakat paid through official institutions can reduce Taxable Income (PKP) for Muslim taxpayers in Indonesia. This research explores how BSI, as an employer, implements its Article 21 Income Tax obligations, as well as the understanding and utilization of the zakat-as-tax-deduction policy among its employees within the operational and marketing work units. Employing a qualitative approach with a case study method, this research will collect data through interviews with BSI employees from the operational and marketing units. The findings are expected to provide a comprehensive overview of the effectiveness of Article 21 Income Tax implementation, employees' level of understanding regarding tax deduction mechanisms, and the extent to which the zakat-as-tax-deduction policy is utilized by BSI employees. The results of this study are anticipated to contribute to the understanding of taxation practices in Islamic financial institutions and provide insights for BSI and related authorities in enhancing the effectiveness of tax policy implementation and zakat utilization.